ANALYSIS OF THE IMPACT OF TRANSVERSUS ABDOMINIS PLANE BLOCK AND INTRATHECAL MORPHINE AS POST-CESAREAN - Bambang Sulistyo; Wisnu Budi Pramono; Wahyudin Wahyudin (Mandala Of Health, 2026)
Background: Surgical wound pain 24 hours after cesarean section is still a problem found in obstetric patients. Many drugs are used to reduce pain scores both orally, intravenously, transdermally and others. However, it is necessary to pay attention to the dosage of the drug so that it does not harm the postoperative patient. Other methods that can be used include preoperative administration of intrathecal morphine and administration of transversus abdominis muscle blocks. Methods :The study's experimental design uses a post-test only control group. Three groups were created from 108 cesarean patients who had no problems. As per standard protocol, the control group (K) had a cesarean section with intravenous analgesia after the procedure. The Intrathecal Morphine (M) group got preoperative intrathecal morphine in addition to the same treatment as the K group. Apart from receiving the same treatment as group K, the Transversus Abdominis Plane Block (B) group also underwent bilateral transversus abdominis muscle blocks guided by ultrasonography. SPSS for Windows Release 26.0 was used to process the data, and differences with a significance level of 0.05 were examined using the One-Way ANOVA test analysis and the Bonferroni Post Hoc test. Outcomes: Group B differed significantly from group K on the visual analogue scale (p value = 0.000). Similar results were obtained for Group M compared to Group K (p value = 0.000). Group B and group M differ significantly from one another, as can be shown, Compared to group M, group B's visual analogue scale is lower (p=0.000). Conclusion: Intrathecal morphine and transversus abdominis block are effective in reducing post-cesarean section pain. Obtained a lower pain score in the administration of transversus abdominis block compared to intrathecal morphine with a significant difference.